The Impact of Product Quality, Service Quality, and Digital Infrastructure Quality on Customer Loyalty: Evidence from Zus Coffee Malaysia - Yee Huei Lok; Lay Hong Tan; Ranjith P. V; Bhupendra Kumar; Wen Xuan Cheng; Zhan Hang Chen; Zi Xian Chen; Pullela Sneha Latha; Hafis Mohammed P; Nida Sarfaraz; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
This study investigates the impact of product quality, service quality, and digital infrastructure quality on customer loyalty at Zus Coffee Malaysia. As competition intensifies in Malaysia’s coffee retail industry, customer retention has become increasingly challenging, especially with the rise of digital platforms and changing consumer expectations. The main objective of this research is to examine how these three dimensions of quality influence customer loyalty among Zus Coffee customers. A quantitative research method was employed through an online survey of 101 respondents across major Malaysian cities. Our findings present that product quality and service quality have a significant positive impact on customer loyalty, while digital infrastructure quality such as mobile app usability and digital payment efficiency also plays a key supporting role. Our study highlights the importance of integrating both physical and digital quality factors to enhance customer loyalty in the coffee industry. Additionally, it offers practical insights for managers seeking to enhance customer satisfaction through strategic improvements in product consistency, service quality and digital infrastructure engagement, aligning with consumers’ expectations for quality and convenience.